Notas biográficas e metáforas religiosas na poesia de Jorge de Lima - Melo, Flavio Ferreira de (2013)
The work we present dissertation, which we titling "Notes Biographical and Religious Metaphors in the Poetry of Jorge de Lima" began with the production of the compendium and fortune of writing still in critical latto sensu, which had as its main concern the analysis of several critical texts on the work jorgiana. Today, but, now with the bibliography with the production of this critical fortune, we look away to the third stage of the poet Jorge de Lima, this third phase devoted to Catholicism, poetry translated poetry and restoration in Christ, beside the poet mineiro Murilo Mendes. The work in question will discuss the importance of Jorge de Lima for National poetry and the Catholic aspect of it, from that, and for that, we will confront biblical and poetic moments along a specific select chosen to illustrate the body of the dissertation